Food Habits of Gray Reef Shark Carcharhinus amblyrhynchos (Bleeker, 1856) - Megawangi, Hestariyani; Rapi, Nuraeni L.; Susaniati, Warda (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Sharks are fish that have a high selling value, so fishermen's interest in catching sharks is also high.The research was carried out from January to November 2021 in the Makassar Strait. Observations were made by dissecting to see the type of food contained in the stomach. The stomach was split open and its contents were removed and then separated according to the type of food, then the type of food was observed directly to identify it. The research results show is the length distribution of long sharks ranges from 49 cm – 251 cm. The relative length of the intestine of 0.7 cm is included in carnivore fish. The highest average value of index of proponderance (%) for sharks was in the tengkek selar food of 52.92%, while the lowest average value of index of proportion was found in the crustacean food of 2.12%. Tetengkek selar is the main food for long sharks, complementary foods are layur fish, squid, crustaceans and fishunidentifiedand additional foodare grouper, anchovies, selar kuning and baronang.The catch of long fish obtained a size structure that varies from small, medium and large. The eating habits of sharks include carnivore fish and eat pelagic and demersal fish.Tetengkek selar is the main food for long sharks, complementary foods are layur fish, squid, crustaceans and fishunidentified.Additional foodare grouper, anchovies, selar kuning and baronang.